2021
DOI: 10.1002/cpt.2485
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Platelet Thromboxane Inhibition by Low‐Dose Aspirin With Platelet Count and Cytoreductive Therapy in Essential Thrombocythemia

Abstract: Essential thrombocythemia (ET) is a myeloproliferative neoplasm characterized by enhanced platelet production and thrombotic complications. The inhibition of platelet cyclooxygenase (COX) activity by the standard once-daily aspirin is mostly incomplete due to accelerated thrombopoiesis. The phase II Aspirin Regimens in EsSential thrombocythemia (ARES) trial has recently compared the efficacy of once-vs. twice-or three-times daily low-dose aspirin in inhibiting platelet thromboxane (TX) A 2 production, as refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Indeed, the ARES phase II trial has recently showed a superior efficacy of multiple (both bid and tid) daily low-dose aspirin regimens in adequately suppressing sTXB 2 , as compared to the standard od regimen [ 31 ]. Moreover, the same trial showed that a tid regimen was similar to a bid regimen in the degree of platelet COX-1 inhibition [ 31 , 35 , 36 ] which is consistent with our in silico prediction ( Fig 7 ).…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, the ARES phase II trial has recently showed a superior efficacy of multiple (both bid and tid) daily low-dose aspirin regimens in adequately suppressing sTXB 2 , as compared to the standard od regimen [ 31 ]. Moreover, the same trial showed that a tid regimen was similar to a bid regimen in the degree of platelet COX-1 inhibition [ 31 , 35 , 36 ] which is consistent with our in silico prediction ( Fig 7 ).…”
Section: Discussionsupporting
confidence: 90%
“…Kwon et al demonstrated a close relationship between inflammatory conditions and the progression of atherosclerosis in myeloproliferative disorder and that reducing inflammation may help to regress plaque [16]. Tosetto et al indicated that platelet count is the most important factor for determining how well oncedaily low-dosage ASA inhibits thromboxane A2 in ET, which may also improve the efficacy of antithrombotic therapy itself [17]. Therefore, it is necessary to suppress the disease state and normalize platelet counts, especially in progressive cases, similar to our own.…”
Section: Discussionmentioning
confidence: 99%
“…No studies have compared the therapeutic efficacy of CLZ and ASA in patients with ET and the JAK2 V617F mutation; however, as previous reports have documented thromboxane metabolite excretion due to platelet activation [19], the administration of aspirin, which inhibits thromboxane A2 (TXA2), is sensible. According to Tosetto et al, platelet count appears to be the most important factor for determining how well once-daily lowdosage aspirin inhibits TXA2 in ET [17].…”
Section: Discussionmentioning
confidence: 99%
“…For references, see Tosetto et al 45 ; Rocca et al 46 ; Petrucci et al The plasminogen/plasmin s ys tem beyond f ibrinolysis: Emerging player s in resolution of inflammation…”
Section: Bianca Rocca MD Phdmentioning
confidence: 99%